Correction of cognitive deficits in mouse models of Down syndrome by a pharmacological inhibitor of DYRK1A - Thu Lan Nguyen; Arnaud Duchon; Antigoni Manousopoulou; Nadège Loaëc; Benoît Villiers; Guillaume Pani; Meltem Karatas; Anna E. Mechling; Laura-Adela Harsan; Emmanuelle Limanton; Jean-Pierre Bazureau; François Carreaux; et al. (The Company of Biologists, 2018)
Growing evidence supports the implication of DYRK1A in the development of cognitive deficits seen in Down syndrome (DS) and Alzheimer's disease (AD). We here demonstrate that pharmacological inhibition of brain DYRK1A is able to correct recognition memory deficits in three DS mouse models with increasing genetic complexity [Tg(Dyrk1a), Ts65Dn, Dp1Yey], all expressing an extra copy of Dyrk1a. Overexpressed DYRK1A accumulates in the cytoplasm and at the synapse. Treatment of the three DS models with the pharmacological DYRK1A inhibitor leucettine L41 leads to normalization of DYRK1A activity and corrects the novel object cognitive impairment observed in these models. Brain functional magnetic resonance imaging reveals that this cognitive improvement is paralleled by functional connectivity remodelling of core brain areas involved in learning/memory processes. The impact of Dyrk1a trisomy and L41 treatment on brain phosphoproteins was investigated by a quantitative phosphoproteomics method, revealing the implication of synaptic (synapsin 1) and cytoskeletal components involved in synaptic response and axonal organization. These results encourage the development of DYRK1A inhibitors as drug candidates to treat cognitive deficits associated with DS and AD.